Material potencialmente significativo e inclusão de estudantes surdos: proposta didática sobre equação do 1o grau com o jogo Lo shu: Potentially meaningful material and the inclusion of deaf students: a didactic proposal about first degree equation with the use of the Lo shu game (Revista Cocar, 2022)
A potencialidade recursiva dos jogos pode ser constatada muito antes da forma como as áreas do conhecimento acadêmico são concebidas nos dias atuais. Na educação inclusiva, as implicações quanto às dificuldades de aprendizagem matemática, carecem de estratégias de ensino que privilegiem a compreensão de significados. Assim, surge a Proposta Didática com o Lo shu para conceituar equação do 1o grau em turmas inclusivas do 8º ano do Ensino Fundamental, embasada no marco teórico ausubeliano. Trata-se de um estudo teórico que investe na compreensão desse conceito, partindo das ideias de regularidade, sequências recursivas e não recursivas, aportado no uso de jogos como recurso didático e nos princípios programáticos ausubelianos. Além do intuito de ampliar as chances de inclusão matemática de surdos, espera-se que tal proposta seja um Material Potencialmente Significativo.Palavras-chave: Material potencialmente significativo, Jogo Lo shu, Inclusão de estudantes surdos. AbstractThe recursive potential of games in social, educational, scientific terms, etc., can be noticed much earlier than the way in which the areas of academic knowledge are conceived today. In inclusive education, considering the multiple implications regarding the difficulties of mathematical learning, there is a lack of teaching strategies that favor the understanding of meanings of algebraic content. Thus, a Didactic Proposal is formulated using the Lo shu for the concept of equation in inclusive classes of the 8th grade of Elementary School, based on the ausubelian theoretical framework. This is a theoretical study, which seeks ways to promote conditions for the development of algebraic thinking, starting from the ideas of regularity, recursive and non-recursive sequences, to understand the concepts of expression and equation, supported by the use of games as didactic resources in Mathematics Education and in progressive differentiation/integrative reconciliation as programmatic principles. In addition to expanding the possibilities for the mathematical inclusion of the deaf, it is expected that this Didactic Proposal will be a Potentially meaningful Material.Keywords: Potentially meaningful Material, Lo shu game, Inclusion of deaf students.